A Computational Approach for Exploring Carbohydrate Recognition by Lectins in Innate Immunity - Agostino, Mark; Yuriev, Elizabeth; Ramsland, Paul A. (Frontiers in Immunology, 2011)
Recognition of pathogen-associated carbohydrates by a broad range of carbohydrate binding proteins is central to both adaptive and innate immunity. A large functionally diverse group of mammalian carbohydrate binding proteins are lectins, which often display calcium-dependent carbohydrate interactions mediated by one or more carbohydrate recognition domains. We report here the application of molecular docking and site mapping to study carbohydrate recognition by several lectins involved in innate immunity or in modulating adaptive immune responses. It was found that molecular docking programs can identify the correct carbohydrate binding mode, but often have difficulty in ranking it as the best pose. This is largely attributed to the broad and shallow nature of lectin binding sites, and the high flexibility of carbohydrates. Site mapping is very effective at identifying lectin residues involved in carbohydrate recognition, especially with cases that were found to be particularly difficult to characterize via molecular docking. This study highlights the need for alternative strategies to examine carbohydrate-lectin interactions, and specifically demonstrates the potential for mapping methods to extract additional and relevant information from the ensembles of binding poses generated by molecular docking.